Índices mínimos de produtividade e cumprimento da função social da propriedade: uma análise da atualidade do grau de eficiência da exploração (GEE) da soja por agrupamentos regionais delimitados pelo INCRA - Silva, Jade Freitas da (Universidade Federal de São Carlos, 2023)
The dynamic nature of the expropriation of unproductive agricultural properties is fundamental in fulfilling the social function of land and reducing social inequalities through Agrarian Reform. In Brazil, indices were designed that provide the basis for calculating the productive efficiency of a crop and attest to the rational and adequate use of land, as provided for in article 186 of the Federal Constitution. These indices were set by the National Institute of Colonization and Agrarian Reform (INCRA), the competent body, back in the 1970s and, therefore, may be out of date. This work aimed to evaluate the adequacy of the exploration efficiency index in relation to current soybean production levels in Brazil. The data were obtained from the IBGE Municipal Agricultural Production (PAM) survey, following the regional groupings established by INCRA. For the purposes of this research, a methodology was introduced to determine minimum levels of productive efficiency, based on distributional characteristics of soybean productivity in regional groupings, enabling the comparison of the current productive scenario with what is predicted as a requirement to attest land productivity, excluding it from the possibility of expropriation for failure to fulfill its social function.
Minimum indexes of productivity and compliance with the social function of the property: an analysis of the current degree of exploration efficiency (GHG) of soybean by regional groupings delimited by INCRA
Keywords: índices mínimos de produtividade; Grau de eficiência na exploração; Função social na propriedade; Reforma agrária; Soja; Minimum productivity indices; Degree of efficiency in exploration; Social function on the property; Agrarian reform; Soybeans; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA